Novel, low-cost, CFRP pressure vessel design for hydrogen fuel cell applications - Mawire, Nyasha Nigel (Department of Mechanical Engineering, 2020)
In 2015, the Ascension III water rocket shattered the previous long-standing world record of 633 m after reaching an altitude of 835 m. This feat was primarily attributed to the design of the Carbon Fibre Reinforced Plastic (CFRP) pressure vessel portion of the rocket. The pressure vessel was composed on a long, thin-walled commercial CFRP cylindrical tube that had two Poly Vinyl Chloride (PVC) end caps bonded onto either end with an adhesive. The inside wall of the CFRP tube was coated with a thin rubber liner to prevent leakage through the tube wall of the pressurised air-water mixture that provided the necessary thrust for the rocket. The outcome was that the CFRP pressure vessel design was thus, novel, low-cost and lightweight with the potential to be used in other gas storage applications for example in Hydrogen Fuel Cell (HFC) applications. This report details the research aimed at identifying the feasibility and suitability of the proposed CFRP pressure vessel concept for high pressure hydrogen gas storage for use in Hydrogen Fuel Cell Powered Vehicles (HFCPVs). The primary component of the pressure vessel to be designed was the CFRP tube which was to be commercially filament wound using carbon fibre and epoxy resin. With an angle ply laminate structure for the CFRP tube, an optimal fibre winding angle of 50° was initially chosen to maximise the burst pressure. The stress analysis and strain behaviour of the CFRP tube were modelled using the Classical Lamination Theory. Specimens were made using the same CFRP material as the tube and were tensile tested to give an initial set of approximate properties to be used in the design calculations. The distinct geometrical features of the end cap were designed, and Aluminium 6082-T6 was selected as a suitable material for its construction as it was easy to machine while it also possessed desirable mechanical properties. SpaBond 340 LV epoxy adhesive was used to bond the end caps onto the ends of the CFRP tube. A number of specimen CFRP pressure vessels were constructed with the inclusion of the rubber liner. Hydrostatic burst tests were performed on specimen vessels with different wall thicknesses (2 mm and 4 mm) to determine the pressure at which each type of vessel would fail. However, only the 2 mm vessels experienced failure of the CFRP tube section as the predominant failure mode while most 4 mm vessels failed by shearing of the interface between the adhesive layer and end cap. According to the ASME Boiler and Pressure Code Section X, the maximum design pressures at which the CFRP pressure vessels could operate at were at most, 2.25 times smaller than the respective failure pressures. The maximum design pressures were thus determined to be 147 bar and 182 bar for the 2 mm and 4 mm CFRP pressure vessels respectively. The specimen pressure vessels were also fitted with strain gauges on the external cylindrical surface of the CFRP tubes to measure the longitudinal and hoop strain during the burst tests. The strain measurements allowed the deformation behaviour of the CFRP tubes to be modelled which would prove useful for designing further CFRP tubes. For all specimen CFRP pressure vessels, it was observed that the deformation response of the CFRP tubes were linear up until a certain pressure. Beyond that point, a decrease in stiffness was observed which suggested that some form of irreparable damage had commenced. Other specimen CFRP pressure vessels were constructed and underwent hydraulic proof testing at 1.25 times the design pressure for 30 minutes and at the design pressure for a further 24 hours. The objective was to assess if the pressure vessels were durable and reliable of which all tested specimen vessels passed successfully. The hydraulic proof test results seemingly suggested that the rubber liner could adequately prevent leakage of water from the vessels at their design pressures. The long-term gas leak test was performed at the design pressure using air (i.e. a compressible fluid) on the proof tested pressure vessels to detect and localize any leaks for a duration of up to 72 hours. However, the leak rates were determined to be at least an order of magnitude larger than the recommended leak rate for hydrogen gas storage vessels. The leak test results strongly suggested that the rubber liner was insufficient to prevent air molecules from escaping the vessel, was not durable for repeated use and thus, not suitable for long-term gas storage. Therefore, it was concluded that the novel CFRP pressure vessel design concept was not yet suitable for hydrogen gas storage, but with improvements, could still prove possible for use in HFCPVs. Further work into these improvements could include improving the end cap design and testing other rubber liners.